2016
DOI: 10.1016/j.ydbio.2016.04.019
|View full text |Cite
|
Sign up to set email alerts
|

The LIM-homeodomain transcription factor Islet2a promotes angioblast migration

Abstract: Angioblasts of the developing vascular system require many signaling inputs to initiate their migration, proliferation and differentiation into endothelial cells. What is less studied is which intrinsic cell factors interpret these extrinsic signals. Here, we show the Lim homeodomain transcription factor islet2a (isl2a) is expressed in the lateral posterior mesoderm prior to angioblast migration. isl2a deficient angioblasts show disorganized migration to the midline to form axial vessels and fail to spread aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…Our previous studies found the vascular functions of Isl2 and Nr2f1b are mediated by Notch signaling 18, 19 . In this study, we demonstrated that cpn1 functions in the vasculature are mediated by VEGF and Notch signals.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Our previous studies found the vascular functions of Isl2 and Nr2f1b are mediated by Notch signaling 18, 19 . In this study, we demonstrated that cpn1 functions in the vasculature are mediated by VEGF and Notch signals.…”
Section: Discussionmentioning
confidence: 94%
“…In our previous study, we identified the function of the transcription factors Isl2 and Nr2f1b in the vasculature mediated by Notch signals 18, 19 . Our Isl2/Nr2f1b transcriptomal analysis suggested that cpn1 acts a potential function in the vasculature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antisense riboprobes were synthesized using T7 polymerase with a DIG RNA labeling kit (Roche) according to the manufacturer’s instructions. The ephrinb2 , mrc1 , flk , and stabilin probes have been described [ 22 , 49 , 50 ]. The whole-mount in situ hybridization protocol was based on Thisse et al [ 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the cellular and molecular mechanisms underlying vascular development have been shown to be conserved in vertebrates. The zebrafish model has been successfully used to reveal molecular mechanisms of blood vessel formation, such as angioblast specification and differentiation, endothelial cell proliferation and migration, vessel formation, patterning, and morphogenesis [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. In addition, the zebrafish model has been widely used to examine the effects of chemicals, drugs, and environmental hormones in vascular development [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%